2020
DOI: 10.1002/anie.201915168
|View full text |Cite
|
Sign up to set email alerts
|

Formation of an Alkynyl‐Protected Ag112 Silver Nanocluster as Promoted by Chloride Released In Situ from CH2Cl2

Abstract: By directly reducing alkynyl–silver precursors, we successfully obtained a large alkynyl‐protected silver nanocluster, (C7H17ClN)3[Ag112Cl6(C≡CAr)51], which is hitherto the largest structurally characterized silver nanocluster in the alkynyl family. The cluster exhibits four concentric core–shell structures (Ag13@Ag42@Ag48@Ag9), and four types of alkynyl–silver binding modes are observed. Chloride was found to be critical for the stabilization and formation of the silver nanocluster. The release of chloride io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
77
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 54 publications
4
77
0
2
Order By: Relevance
“…[11] Thef ive types of complex coordination modes of alkynes on the surface of metal clusters are described in literatures,w hich can tune their electronic structure through p-conjugation. [12] Recently,Wang et al reported aseries of structurally precise alkynylate metal clusters including:(a) mixed alkyne and phosphine protected monometallic clusters, [13] namely Au 19 (dppp:b is(diphenylphosphino)-pentane), and (b) the homoleptic alkyne protected gold clusters, [14] 26 .I na ddition, the crystal structures of Au-Ag bimetallic clusters with composition, [15] were found to be very stable over aperiod of month or more under the ambient conditions.H owever, still some issues are there to be addressed:( 1) the aforementioned Au 34 Ag 28 [15a] is the onlyexample of homoleptic alkynylated Au and Ag bimetal cluster with precise crystal structure and (2) so far, the phenyl acetylene that is,t he simplest known aromatic alkyne has been regularly used to protect the metal clusters.F urthermore,o nce the phenyl group is replaced or an ew functional group is added to phenyl group,i ts effect on coordination model, structure and properties remained unclear. Hence,i n order to expand the library of homoleptic alkynylated Au and Ag bimetal cluster for gaining deep insight, it becomes essential to synthesize and determine the precise structure of the novel bimetal nanoclusters protected by atypical homoleptic alkyne ligands.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Thef ive types of complex coordination modes of alkynes on the surface of metal clusters are described in literatures,w hich can tune their electronic structure through p-conjugation. [12] Recently,Wang et al reported aseries of structurally precise alkynylate metal clusters including:(a) mixed alkyne and phosphine protected monometallic clusters, [13] namely Au 19 (dppp:b is(diphenylphosphino)-pentane), and (b) the homoleptic alkyne protected gold clusters, [14] 26 .I na ddition, the crystal structures of Au-Ag bimetallic clusters with composition, [15] were found to be very stable over aperiod of month or more under the ambient conditions.H owever, still some issues are there to be addressed:( 1) the aforementioned Au 34 Ag 28 [15a] is the onlyexample of homoleptic alkynylated Au and Ag bimetal cluster with precise crystal structure and (2) so far, the phenyl acetylene that is,t he simplest known aromatic alkyne has been regularly used to protect the metal clusters.F urthermore,o nce the phenyl group is replaced or an ew functional group is added to phenyl group,i ts effect on coordination model, structure and properties remained unclear. Hence,i n order to expand the library of homoleptic alkynylated Au and Ag bimetal cluster for gaining deep insight, it becomes essential to synthesize and determine the precise structure of the novel bimetal nanoclusters protected by atypical homoleptic alkyne ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Such phenomenon has also observed in several other metal nanoclusters such as in Ag 44 ,A g 40 ,A g 112 and Au 18 . [3,7,22] Anyway,a ll other 14 species excepting for 1h can directly or indirectly evidence the + 4c harge state of SD/Ag78a.…”
Section: Forschungsartikelmentioning
confidence: 99%
“…Years of research on ligand-protected nanoclusters have promoted the advance in various aspects. [1][2][3][4][5] With different kinds of protecting agents including phosphine, [6][7][8][9][10][11] thiolate, [12][13][14][15][16][17][18][19][20] alkynyl, [21][22][23][24][25][26][27][28][29] and amido ligands [30,31] applied in use, alarge number of metal nanoclusters have been synthesized, and their interesting optical and catalytic properties have been also well studied. [32][33][34] Owing to applications in chiral sensing,enantioselective catalysis,biological applications and optical devices, [35][36][37][38][39][40][41][42][43] chiral materials have become irreplaceable in chemical research.…”
Section: Introductionmentioning
confidence: 99%